Innovative Model for Assessing the Level of Failure Risk in Construction and Buildings - Sayfuddin, S.; Adi, Henny Pratiwi; Pentenga, Tom Joy (JACEE (Journal of Advanced Civil and Environmental Engineering), 2024)
This research explores risk management in construction projects to prevent potential failures due to natural factors or human errors. The objective is to develop a risk assessment model for failures in construction and building projects, focusing on identification, categorization, risk level determination, and model development. The research benefits encompass theoretical contributions to construction risk management, governmental policy guidelines, operational assistance in project risk management, and enhancements in the safety and quality of construction projects. This research innovates by expanding research variables, incorporating failure risk level assessments, and utilizing technological approaches. The research methodology combines quantitative and descriptive approaches, focusing on failure risk factors from service/contractor providers, consultants, and project owners. Data is obtained through literature studies, secondary data, and primary data via questionnaires. The analysis involves factor analysis, importance index, impact probability matrix, and the Partial Least Square (PLS) method for structural analysis. The research conclusion identifies failure risk factors including financial aspects, management, equipment availability, and natural impacts such as floods and earthquakes. The risk assessment model categorizes risks into high, medium, and low, enabling appropriate anticipatory measures. This model provides guidance for stakeholders to mitigate risks, improve quality, and maintain the integrity of construction projects and buildings, supporting safety and success throughout project stages. This research makes a significant contribution to construction project risk management and construction quality improvement.